Obesity–cancer axis crosstalk: Molecular insights and therapeutic approaches - Ahmed Rakib; Md Abdullah Al Mamun; Mousumi Mandal; Priti Sinha; Udai P. Singh (Acta Pharmaceutica Sinica B)
Now recognized as a global health crisis, obesity has been linked to an increased risk of many types of cancer, including those of the breast, colon, rectum, uterus, gallbladder, and ovary. Obesity and cancer share several characteristics at the cellular, molecular, and epigenetic levels. Obesity is characterized by chronic inflammation of the adipose tissue (AT), resulting in genotoxic stress that further induces metabolic complications and contributes to the initiation and progression of cancer. The excessive accumulation of AT provides adipokines and lipids to engage tumor cells with stromal and immune cells to infiltrate carcinomas and secrete a plethora of cytokines, chemokines, and growth factors within the tumor microenvironment (TME) that contribute to carcinogenesis. Obesity also alters the metabolic reprogramming of immune cells, including macrophages, neutrophils, and T cells, thereby providing a suitable environment for the growth and progression of cancer. Obesity-associated metabolic dysregulation also perturbs the gut microbiome, which produces metabolites that can further increase the risk of cancer progression. This review will discuss links between obesity and cancer progression, including several crucial pathways that bridge the crosstalk between obesity-associated changes in AT inflammation, immune cells, adipokines, chemokines, and tumor cells to support cancer progression. We will also discuss our insights into the mechanisms by which obesity-driven factors influence metabolic reprogramming and touch base on how obesity mediates microbiome dysbiosis to alter metabolite and affect cancer progression. Altogether, this review highlights the crossroads of the obesity–cancer axis, describes its salient features, and presents possible therapeutic approaches for obesity-related cancers.